Artificial intelligence : structures and strategies for complex problem solving - Luger, George F. (Boston : Pearson Addison-Wesley, 2009)
In this accessible, comprehensive text, George Luger captures the essence of artificial intelligence-solving the complex problems that arise wherever computer technology is applied. Key representation techniques including logic, semantic and connectionist networks, graphical models, and many more are introduced. Presentation of agent technology and the use of ontologies are added. A new machine-learning chapter is based on stochastic methods, including first-order Bayesian networks, variants of hidden Markov models, inference with Markov random fields and loopy belief propagation. A new presentation of parameter fitting with expectation maximization learning and structure learning using Markov chain Monte Carlo sampling. Use of Markov decision processes in reinforcement learning. Natural language processing with dynamic programming (the Earley parser) and other probabilistic parsing techniques including Viterbi, are added. A new supplemental programming book is available online and in print:'AI Algorithms in Prolog, Lisp and Java (TM).'References and citations are updated throughout the Sixth Edition. For all readers interested in artificial intelligence.
Includes bibliographical references (p. 705-733) and indexes.
Buku bacaan asas fakulti
Keywords: Artificial intelligence; Knowledge representation (information theory).; Problem solving; Prolog (Computer program language).; LISP (Computer program language).